Some considerations on common noise criteria - MYNCKE, H. (Archives of Acoustics, 1985)
Until now the ideal noisedescriptor has not been invented. The purpose of this paper is to draw the attention of the user to some shortcomings of common noise criteria in extreme circumstances. Comments are made on the A-weighted sound pressure level L_A, the continuous equivalent sound pressure level L_Aeq, the sound exposure level L_AE, and the percentile levels L_AN. These comments do not affect the usefulness of these descriptors.